Implementación de normas técnicas para la producción de queso en APRODEMAG. - Jeréz Cevallos, Diana Verónica (2019)
In this project it was possible to implement a Manual of Good Manufacturing Practices (GMP) in “APRODEMAG”. To ensure the development of the manual; previously the initial situation of the company was assessed through a checklist that was based on the requirements of the standard of Good Manufacturing Practices (GMP) for processed foods N.3253 in 2002. It was aimed at evaluating the next 8 items: facilities, equipment, and utensils, hygienic production, raw materials and inputs, production operations, packaging, labeling, storage, distribution, transportation and marketing, quality assurance and control. After assessing the initial situation of the company was obtained as a result that 42.38% comply with the provisions of the official register, 41.72% did not comply and finally a 15.39% does not apply, with that data the proposal to improve the implementation of the manual was developed. The proposed study is presented as a nonexperimental research and a field modality is adopted, using tools such as direct observation and document review according to the needs of the company, using standard operating procedures (SOP, standard operating procedure of sanitation (SOPS) and critical control points (CCP) where it can be identify the risks that may exist, therefore preventive measures, corrective, throughout the production process were established. With the information gathered, the safety is guaranteed in the process of developing the product; fresh cheese, from the beginning of the raw material to the distribution to the direct consumer, allowing to reduce operating costs and improve quality.